2011
DOI: 10.1002/ir.380
|View full text |Cite
|
Sign up to set email alerts
|

Developing and assessing college student teamwork skills

Abstract: This chapter describes research on team member contributions to overall team effectiveness, and various applications of this research to developing and assessing teamwork by students on team and group projects and assignments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 19 publications
7
73
0
8
Order By: Relevance
“…CATME responded by offering an abbreviated instrument containing 33 questions (Hughes & Jones, 2011), which some believe remains too long (Ohland et al, 2012).…”
Section: )supporting
confidence: 42%
See 1 more Smart Citation
“…CATME responded by offering an abbreviated instrument containing 33 questions (Hughes & Jones, 2011), which some believe remains too long (Ohland et al, 2012).…”
Section: )supporting
confidence: 42%
“…Collaboration is a synergistic, voluntary combining of individual contributions for a collective goal (Hughes & Jones, 2011;Thomas et al, 2007). Viability of collaboration can be threatened, such as by interpersonal conflict, poor strategy, or selfish manoeuvring (Chen, Ünal, Leung, & Xin, 2016;Topping, 2010).…”
Section: Measuring Collaboration Viabilitysupporting
confidence: 42%
“…Aunque en la literatura existen algunos trabajos importantes relacionados con el tema [véase por ejemplo (Glinz, 2005;Hughes & Jones, 2011)], hasta donde se conoce estos están enfocados a establecer solamente directrices sobre cómo formar los equipos, o los beneficios de emplear este recurso educativo. Esto es, se asume que el docente es quién debe realizar esta tarea de forma manual.…”
Section: Introductionunclassified
“…Generally, engineering faculty view teaming skills as valuable to engineering students and collaborative learning provides an opportunity for students to practice professional skills while in college. Additionally, multiple studies have identified teamwork as one of the most valued and necessary skills for college graduates, as the majority of engineering employers want engineering educators to focus on developing students' teaming and collaboration skills [7] . Despite the clear emphasis on teamwork in engineering and the increasing use of student team projects, our understanding of how to support engineering students to develop these skills is limited [1] .…”
Section: Introductionmentioning
confidence: 47%